Design of non-linear mathematical function - Lim, Wei Yi. (2010)
The title of the author’s final year project (FYP) is “Design of Non-linear Mathematical function”. In this report, the author has covered on a squarer circuit [3] and a logarithmic function circuit [4], with focus mainly on the squarer circuit. During the initial stage of the project, mathematical derivation and application based on circuit knowledge will be employed to deduce suitable parameters/specifications for the two circuits. After that, both circuits will be designed using simulation tools such as “LTspice” and “Electric”, simulated results will then be compared with theoretical data with detailed discussion in chapter 3 and chapter 9 of the report respectively. In addition, the author will be providing suggestions on how to further enhance performance of circuits in the report, for instance to change the simple current mirror configuration of the core cell of the squarer circuit to cascade current mirror configuration, by doing so, the current mirror mapping of transistors within the circuit will improves and this ultimately improves the performance of circuit, more elaborated discussion is done in chapter 5 of report. Apart from this, suitable processes will also be downloaded from link [12] and implemented on the squarer circuit to illustrate how different processes will affect the circuit performance. Lastly, a layout of half of the squarer circuit will be drawn using “Electric”, the purpose of drawing the layout is to enable the author to learn how to view circuit in 3-dimensional form and to be able to appreciate the difficulty in making a compact circuit layout. The output of the schematic diagram will be compared with output of the layout to ensure that the author has successfully designed the layout of the circuit.